Facing the Music: The Dubious Constitutionality of Facial RecognitionTechnology - Brogan, John J. (2002)
Recent advances in biometric identification technology, along with ever more extensive databases of information about ordinary citizens, inspire concern among civil liberties advocates about whether there are any meaningful limits on government's ability to keep track of ordinary citizens. In this Article, Professor Brogan discusses facial recognition technology, and argues that courts should draw a distinction between wide area scans, which should be severely limited or banned, and focused facial scans, which may be allowable under limited circumstances involving particularized suspicion